Feasibility of the general examination system for primary study An exploratory study - محمد عبدالحسن ناصر, م.د. (lark, 2021)
Our current study examines the feasibility of continuing the general examinations system for primary school in particular, taking into account the opinions of the principal actors in the educational work, including teachers, educational supervisors, and primary school administrators, as well as comparing the results of the annual pursuit before the general examinations, and the results of the public examinations for the sixth stage Primary.The study concluded: There is no agreement to maintain or cancel the general examinations regarding the opinions of teachers, educational supervisors, and school directors, and each team has its own justifications that support its orientation. It is to make the final examination for the primary stage a school examination under the supervision and supervision of the principals of middle schools fed by primary schools and their owners.
Keywords: feasibility study, general examinations, primary schools